THE INFLUENCE OF BPUM ON THE REGIONAL ECONOMY DURING THE COVID-19 PANDEMIC - Rifai, Muhammad Darmawan; Djamaluddin, Sartika (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The research objective is to analyze the influence of BPUM on the Regional Economy by considering HDI, poverty levels, PAD and labor force in MSMEs. This type of quantitative research uses panel data, namely secondary archival data on the population of Micro, Small and Medium Enterprises in cities and districts in all provinces in Indonesia. Data was obtained from the Ministry of Cooperatives, Small and Medium Enterprises, the Directorate General of Fiscal Balance (DJPK) and the Central Statistics Agency (BPS) for the period 2020 and 2021. The research population for all districts in Indonesia in 2020 and 2021 was 514 districts and cities. Based on the results of the Fixed Effect Model, the influence of BPUM on GRDP obtained a coefficient value of 0,010803, the influence of HDI on GRDP obtained a coefficient value of -0,0006866, the influence of poverty levels on GRDP obtained a coefficient value of 0,0212617, the influence of PAD on GRDP obtained a coefficient value amounting to 0,0009767, and the influence of the labor force on GRDP obtained a coefficient value of -0,0331359.